2014
DOI: 10.1177/1528083714557057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of argon and air plasma treatment of flax fiber on mechanical properties of reinforced polyester composite

Abstract: Flax fibers were modified by argon and air atmospheric pressure plasma treatments to improve the mechanical properties of flax fiber-reinforced unsaturated polyester composites. Plasma treatments were carried out at plasma powers of 100, 200, and 300 W. Both plasma surface treatments were conducted to improve the tensile strength, tensile modulus, flexural strength, flexural modulus, interlaminar shear strength (ILSS), Mode I interlaminar fracture toughness (G IC ), and Mode II interlaminar fracture toughness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 56 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…As well known, with the aim of improving the compatibility between lignocellulosic fibers and polymeric matrices, fiber surface modification is commonly carried out via physical or chemical methods both leading to reduction in moisture gain, in addition to alterations in the surface properties of vegetal fiber. Physical methods such as plasma 79 and corona treatments 10,11 alter the surface properties of vegetal fibers without alteration of their chemical composition, thus enhancing the mechanical bonding between fiber and matrix. These treatments are mainly used because they do not involve any pollution and can be considered as dry and clean.…”
Section: Introductionmentioning
confidence: 99%
“…As well known, with the aim of improving the compatibility between lignocellulosic fibers and polymeric matrices, fiber surface modification is commonly carried out via physical or chemical methods both leading to reduction in moisture gain, in addition to alterations in the surface properties of vegetal fiber. Physical methods such as plasma 79 and corona treatments 10,11 alter the surface properties of vegetal fibers without alteration of their chemical composition, thus enhancing the mechanical bonding between fiber and matrix. These treatments are mainly used because they do not involve any pollution and can be considered as dry and clean.…”
Section: Introductionmentioning
confidence: 99%
“…Several surface treatment techniques for carbon fibers have been developed such as thermal treatment, wet‐chemical oxidation, electrochemical oxidation, beam irradiation, plasma treatments, and so forth . Being more convenient and fast method with none or little impact on the fiber bulk properties, atmospheric pressure plasma treatments on carbon fibers have drawn a significant attention over the last decades . Many studies reported that wettability of fibers with polymer matrix is improved as a result of plasma treatments due to increased surface energy of fibers and decreased contact angle .…”
Section: Introductionmentioning
confidence: 99%
“…In order to be able to correct this, the polarity, roughness, reactivity and wettability of the reinforcement surface must be changed without changing the bulk properties. [1][2][3][4][5] In studies carried out on composite materials containing natural reinforcements, the surface treatment of natural reinforcement by chemical methods is quite common. [6][7][8][9] But, the length of the chemical treatment process and the environmental damage caused by the chemicals has led to a tendency towards the alternatives to this method in recent years.…”
Section: Introductionmentioning
confidence: 99%